The Effect of a Motivation-Based STAD Learning Model on Students’ Academic Achievement in Mathematics and Science - Partono Siswosuharjo; Al-Bahra Al-Bahra; Andri Cahyo Purnomo; Ewin Suciana (Newinera Publisher, 2026)
This study examined the effectiveness of a motivation-based Student Teams Achievement Division (STAD) learning model on junior high school students' academic achievement in mathematics and science in Banten Province, Indonesia. Employing a quasi-experimental non-equivalent control group design, 750 students were purposively selected through stratified cluster sampling and assigned to experimental (n = 375) and control (n = 375) groups. The experimental group received the motivation-enhanced STAD intervention, while the control group experienced conventional instruction. Data were collected using validated achievement tests and a learning motivation questionnaire, then analyzed through Multivariate Analysis of Covariance (MANCOVA), controlling for pretest scores, prior GPA, socioeconomic status, and age. Results revealed a statistically significant multivariate difference between groups for combined mathematics and science posttest scores (Wilks' Λ, p < 0.001). Univariate ANCOVA further indicated that the experimental group significantly outperformed the control group in mathematics (F(1,743) = 905.38, p < 0.001, η² = 0.549) and science (F(1,743) = 684.56, p < 0.001, η² = 0.479), with large effect sizes. These findings demonstrate that integrating motivational scaffolds such as autonomy support, competence feedback, and positive interdependence within cooperative learning structures substantially enhances both cognitive achievement and affective engagement. The study concludes that the motivation-based STAD model represents a scalable, equity-promoting pedagogical innovation suitable for improving STEM education outcomes in diverse secondary school contexts.